Digital Competence as a Moderating Variable in the Influence of Accounting Information Systems on Financial Reporting Quality - Jhon, Hasinggaan; Atikasari, Dinda; Pahena, Jihan; Rangkuti, Asri Rama Gita; Irawan (CV Raskha Media Group, 2025)
This study aims to analyze the effect of digital competence on the quality of financial reports, with the accounting information system (AIS) serving as a mediating variable. The research adopts a quantitative approach using Partial Least Squares Structural Equation Modeling (PLS-SEM) with data obtained from 100 observations. The path coefficient analysis reveals that digital competence has a negative and insignificant direct effect on the quality of financial reports (-0.016). However, digital competence has a positive and significant effect on AIS (0.989), and AIS, in turn, has a positive and significant effect on the quality of financial reports (1.016). The indirect effect analysis indicates that AIS fully mediates the relationship between digital competence and the quality of financial reports, with an indirect effect value of 1.004. The R-square values for the quality of financial reports and AIS are 0.999 and 0.977, respectively, indicating that the model has very high predictive power. In conclusion, digital competence does not directly improve the quality of financial reports; however, its contribution is highly crucial through the strengthening and effective utilization of accounting information systems. The implications of this study highlight the importance of investing in the development of reliable AIS to transform digital competence into improvements in the quality of financial information.